The implementation of the genre-based approach in the teaching of writing to engineering students / Piyatida Changpueng - Changpueng, Piyatida (Universiti Teknologi MARA Shah Alam, 2017)
Good communication skills are a requirement for all professionals. As for engineers, it seems that writing is one of the most important communication skills to help them to be successful in their professional life. However, many engineering students are poor in writing. Numerous studies havebeen conducted to determine the effectiveness of the different methods used to develop the writing skills of language learners, including the genre-based framework. The present study aims at examining the writing achievement of Thai engineering students receiving writing instruction through the explicit genre-based approach, or GBA (SFL genre), and their attitudes toward this method of teaching. The participants were 28 fourth-year engineering students enrolled in a basic writing course. One lesson in teaching writing recounts was provided during three sessions. The results of a T-test revealed clear improvement in the students' writing ability after attending the lesson. Regarding the attitudes of the students, the findings were crosschecked with the students' responses to the questionnaire, to the interview questions, and in their journal. It was found that the students had a satisfactory attitude toward this teaching method. Based on the study findings, it is recommended that language teachers incorporate the knowledge of genre, genre analysis, and schematic features of a particular genre in their teaching in order to enhance their students' writing proficiency and confidence.